SKATR: a self-supervised summary transformer for SKA - Ore, Ayodele; Heneka, Caroline; Plehn, Tilman (SciPost physics, 2025)
SciPost Journals Publication Detail SciPost Phys. 18, 155 (2025) SKATR: A self-supervised summary transformer for SKA